2023
DOI: 10.1002/adma.202311018
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Phosphine‐Plasma‐Assisted Ultrafast Synthesis of Halogen‐Doped Ru/RuP2 with Surface Intermediate Adsorption Modulation for Efficient Alkaline Hydrogen Evolution Reaction

Zexing Wu,
Qichang Li,
Guangrui Xu
et al.

Abstract: Anionic modification engineering is a crucial approach to develop highly efficient electrocatalysts for hydrogen evolution reaction. Herein, halogen elements (X = Cl, Br, and I)‐modified Ru‐based nanosheets (X‐Ru/RuP2) are designed by rapid and eco‐friendly microwave‐phosphide plasma approach within 60 s. Experimental and density functional theory calculations verify that the introduced halogen element, especially Br, can optimize the surface intermediates adsorption. Specially, the designed Br‐Ru/RuP2 favors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 91 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…For Cr 2 O 3 and CrN, the rate-determining step (RDS) is the last step, *OOH + OH – – e – > * + O 2 + H 2 O, where * is the electrocatalyst. The RDS for the CrO 3 model is as follows: *O + OH – – e – > *OOH. The reaction energy barriers for the RDS are 1.13, 1.20, and 1.10 eV for Cr 2 O 3 , CrN, and CrO 3 models, respectively. That is, CrO 3 has a much smaller barrier than CrN and Cr 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…For Cr 2 O 3 and CrN, the rate-determining step (RDS) is the last step, *OOH + OH – – e – > * + O 2 + H 2 O, where * is the electrocatalyst. The RDS for the CrO 3 model is as follows: *O + OH – – e – > *OOH. The reaction energy barriers for the RDS are 1.13, 1.20, and 1.10 eV for Cr 2 O 3 , CrN, and CrO 3 models, respectively. That is, CrO 3 has a much smaller barrier than CrN and Cr 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…1,2 The global scientific community has suggested that the future energy pathway should be carbon-neutralization to tackle these environmental challenges and lessen the ecosystem damage caused by burning of fossil fuels. 3,4 To date, various technologies such as solar power, wind power, hydropower, and hydrogen fuel cell systems have been developed as alternatives to conventional fossil fuels, aiming to harness clean and sustainable energy sources. 5−7 Also, in recent years, electrochemical energy generation techniques have received much attention due to their capability to supply clean, renewable energy on a large scale.…”
mentioning
confidence: 99%
“…Engineering highly efficient and sustainable electrocatalysts has become a significant area of research due to the ever-growing energy needs, energy crisis, and increasing global warming, which has forced us to emphasize the development of clean, green, and sustainable energy production technologies. , The global scientific community has suggested that the future energy pathway should be carbon-neutralization to tackle these environmental challenges and lessen the ecosystem damage caused by burning of fossil fuels. , To date, various technologies such as solar power, wind power, hydropower, and hydrogen fuel cell systems have been developed as alternatives to conventional fossil fuels, aiming to harness clean and sustainable energy sources. Also, in recent years, electrochemical energy generation techniques have received much attention due to their capability to supply clean, renewable energy on a large scale. Green hydrogen, generated through electrochemical processes, is widely regarded as a highly promising alternative for fulfilling future energy demands.…”
mentioning
confidence: 99%
See 2 more Smart Citations